PROFESSIONAL DEVELOPMENT IN BASIC EDUCATION: PERSPECTIVES FOR TEACHER TRAINING - hobold Soares, Alessandra; Batisti Desbesell Borba, Elizangela; Trindade de Oliveira, Suéli (Revista Gênero e Interdisciplinaridade, 2024)
This article seeks to explore the perspectives and challenges faced by teachers in the context of basic education in relation to professional development. Based on an analysis of training practices and public policies aimed at teacher training, we will discuss the main trends and innovations that have emerged in the field, in addition to offering reflections on how these initiatives directly impact the quality of teaching and student learning. To this end, a bibliographical research was developed to find academic productions, finding authors who research on the subject, expanding the theoretical repertoire. Professional development in basic education faces challenges due to recent transformations in the educational environment. The search for quality, equitable and inclusive education becomes increasingly complex in view of the realities found in schools. In recent years, the profile of children has changed, requiring new didactic and practical approaches from educators. This evolution requires the creation of more dynamic learning environments and the use of innovative resources that can meet the diverse needs of students. Therefore, it is essential that education professionals reflect on their methodologies and seek alternatives that provide new meanings to the contemporary educational system. These changes not only challenge educators to adapt, but also offer opportunities for the implementation of pedagogical practices that promote more collaborative and student-centered teaching. It was concluded, therefore, that continuing teacher training is essential for us to meet the current and future demands of basic education.